THE INFLUENCE OF CUSTOMER REVIEW, BRAND EXPERIENCE AND CUSTOMER SATISFACTION ON REPURCHASE INTENTION IN CARE PRODUCTS MS GLOW IN MEDAN CITY - Suci Chasara Nasution; Endang Sulistya Rini; Prihatin Lumbanraja (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
MS Glow is one of skincare product brands. Glow in Medan City. Currently there has been a decline in sales of MS Glow care products, this is thought to be due to a lack of interest from the people of Medan City to repurchase MS Glow care products. Low repurchase intention must be addressed immediately considering the increasingly competitive beauty industry in Indonesia. This research aims to determine and analyze the influence of Customer Reviews, Brand Experience and Customer Satisfaction on Repurchase Intention in Care Products MS. Glow in Medan City. The population in this study is the people of Medan City who use MS treatment products. Glow. The sampling technique in this research was non-probability sampling using accidental sampling of 180 respondents. The data analysis method uses Multiple Linear Regression Analysis. The research results show that Customer Reviews have a positive and significant effect on Repurchase Intention. Brand Experience has a positive and significant effect on Repurchase Intention. Customer Satisfaction has a positive and significant effect on Repurchase Intention. Customer Reviews, Brand Experience and Customer Satisfaction have a positive and significant effect on Repurchase Intention.